2005
DOI: 10.2307/25065369
|View full text |Cite
|
Sign up to set email alerts
|

Further disintegration of Scrophulariaceae

Abstract: A phylogenetic study of plastid DNA sequences (ndhF, trnL/F, and rps16) in Lamiales is presented. In particular, the inclusiveness of Scrophulariaceae sensu APG II is elaborated. Scrophulariaceae in this sense are mainly a southern hemisphere group, which includes Hemimerideae (including Alonsoa, with a few South Americanspecies), Myoporeae, the Central American Leucophylleae (including Capraria), Androya, Aptosimeae, Buddlejeae, Teedieae (including Oftia, Dermatobotrys, and Freylinia), Manuleeae, and chiefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
248
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(275 citation statements)
references
References 53 publications
20
248
3
4
Order By: Relevance
“…Published DNA sequence-based estimates of relationships among Orobanchaceae lineages have recovered conflicting relationships for Lindenbergia. It has been recovered as sister to the rest of the family excluding Rehmannia (Young et al 1999;Oxelman et al 2005;Wolfe et al 2005). Alternatively, it has been recovered as sister to a small group of parasitic species (represented by species in the genera Bungea, Cymbaria, Monochasma, Schwalbea, and Siphonostegia), with Lindenbergia plus this group as sister to the rest of Orobanchaceae (Bennett and Mathews 2006).…”
Section: Sister-taxon Comparisonsmentioning
confidence: 99%
“…Published DNA sequence-based estimates of relationships among Orobanchaceae lineages have recovered conflicting relationships for Lindenbergia. It has been recovered as sister to the rest of the family excluding Rehmannia (Young et al 1999;Oxelman et al 2005;Wolfe et al 2005). Alternatively, it has been recovered as sister to a small group of parasitic species (represented by species in the genera Bungea, Cymbaria, Monochasma, Schwalbea, and Siphonostegia), with Lindenbergia plus this group as sister to the rest of Orobanchaceae (Bennett and Mathews 2006).…”
Section: Sister-taxon Comparisonsmentioning
confidence: 99%
“…However, recent extensive molecular investigations of this and related families have demonstrated that traditional Scrophulariaceae is polyphyletic (Olmstead & Reeves, 1995;Olmstead et al, 2001;Oxelman et al, 2005). As a consequence of these results, the genus Veronica has been transferred to the Plantaginaceae Olmstead, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular phylogenetic part of the study is based on three DNA regions, the nuclear ribosomal ITS region (3´end of 18S rDNA, ITS1, 5.8S rDNA, ITS2, 5´end of 26S rDNA), the trnL-F region (trnL intron, trnL 3´ exon, trnL-F spacer) and the rps16 intron. All regions have been used before in phylogenetic studies of Lamiales and Scrophulariaceae (e.g., Albach et al 2005;Oxelman et al 2005). …”
Section: Introductionmentioning
confidence: 99%